The Effect of Work Conflict And Work Ethics on The Performance of Civil Servants at The Inspectorate of The Regency of The Mentawai Islands - Zendrato, Sakharia; Khairul, Khairul; Pratomo, Hurip (Journal of World Science, 2022)
Introduction: This study aims to analyze the effect of a work conflict and work ethics on the performance of Civil Servants at the Mentawai Islands Regency Inspectorate. This is motivated by work conflicts within the institution, low work ethics in carrying out work, and employee performance that is still unstable and can be maximized at the Mentawai Islands Regency Inspectorate. Method: This type of research uses a quantitative approach with a multiple linear regression method. Data collection techniques with questionnaires. The respondents of this study were 38 civil servants in the Inspectorate of Mentawai Islands Regency. The sampling method used the total sampling method, where the entire population in this study was used as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0. Results: analysis of the effect of work conflict (X1) and work ethic (X2) together on performance (Y) obtained an F-count value of 30.213 with a significant probability. from 0.000 < 0.05. With df1 = (k-1) = (3-1) = 2, df2 = 38 - 3 = 35, F-table 3.27, then F-count > F-table or 30.213 > 3.27. Consequently, Ho is rejected, and Ha or Hypothesis Three is accepted. The analysis results show that together there is a significant influence between the variables of a work conflict and work ethic on the performance of Civil Servants at the Inspectorate of Mentawai Islands Regency. Conclusion: This study found that work conflict partially and negatively affects performance, and work ethic has a positive and significant effect on performance. In addition, work conflict and work ethic significantly affect the performance of Civil Servants at the Mentawai Islands Regency Inspectorate.